Clinical presentation and non-invasive diagnosis of right heart masses. Issue 5 (November 1981) - Stern, M J; Cohen, M V; Fish, B; Rosenthal, R
Abstract : Right-sided cardiac masses do not have a uniform clinical presentation. Successful diagnosis is dependent on a high index of suspicion and appropriate echocardiographic examination. Five cases of right sided intracardiac masses have been detected during the period that echocardiography has been routinely available to us--two of right atrial myxoma, one of right atrial thrombus, and two of right ventricular tumour. M-mode echocardiography identified four of the five cases. Two-dimensional echocardiography was necessary to establish the non-invasive diagnosis in the fifth case. Echocardiography should be used in any patient in whom a right sided mass is suspected, or in those patients presenting with signs of tricuspid regurgitation, tricuspid stenosis, pulmonary stenosis, cyanotic heart disease, progressive right heart failure, constrictive pericarditis, or pulmonary emboli without obvious source.